EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH COUNTER PRESSURE MASSAGE PADA PENURUNAN NYERI PERSALINAN FASE AKTIF - Hapsari, Puspa; Noviani Fadilah, Lola; Widiawati, Ida (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Labor pain is a physiological thing that happens to mothers during the labor process. During labor, the head in the pelvic cavity will shrink due to pressure on the dorsal nerve which causes pain to the mother during labor. Pain during childbirth is one of the factors that causes mothers to feel that giving birth is a painful. Differences in pain responses are also influenced by past experiences, anxiety and emotional tension. Through experience, a person develops various mechanisms to deal with pain. Emotional tension due to anxiety and fear of the birthing process can aggravate the perception of pain, and vice versa, pain induces fear which causes anxiety and can end in panic. Purpose : This Evidence Based Case Report is to prescribe differences in pain intensity during the first active phase of labor before and after application of counterpressure massage. Method : A search for articles regarding the effect of counterpressure massage was carried out on the Scholar e-database and the Garuda Portal. Result : The intensity of pain before being given Counterpressure massage obtained a value of 8 (very sever) while after being given Counterpressure massage obtained a value of 5 (moderate pain). Conclusion : counterpressure massage is effective in reducing labor pain.